Elaboração de curvas de suportabilidade para microcomputadores e estudo de desempenho de dispositivos mitigadores para subsidiar os PID S - Martins, Edélcio Antônio (2012)
The deregulation of the electricity sector and the evolution in the legislation related to the consumers right and economy growth - with the inclusion of more people in higher classes - have had a strong impact on the relationship between energy distribution companies and electricity consumers. The Strong management of Regulatory Agencies, with frequent application of penalties, has stimulated scientific research by the distribution companies and universities to identify the main causes of the conflicting aspects involving the consumer, the regulator and the energy concessionaire. In this context, a field of study that has generated growing importance is regarding the increase in requests for damage compensation to electronic equipment. If in a way the volume of requests and financial amount to cover these requests have rose highly on another way the lack of efficient mechanisms for analyzing the causal relationship between damage and motivator, has prevented consistent and conclusive analysis, multiplying the claims next to the ombudsman service. This work has as its main objectives: the construction of more real supportability curves from destructive tests and the proposed methodology; the inclusion of such curves in the new version of the APR software (developed in this study); the construction of a friendlier interface for importing data from the georeferenced system of the Energy Concessionaire for the mentioned software, in addition to conducting trials to test the effectiveness of mitigation devices known as DPS. Studies to guide the data were collected by the concessionaire CEMIG D, which guided the analysis for microcomputers, which have been used increasingly and also have had a larger volume / amount of money in requests for damages.